Wrestling for beginners - Jarman, Tom; Hanley, Reid M., 1945- (Chicago : Contemporary Books, 1983)
Gives novice wrestlers those techniques which serve as the foundation for all wrestling instruction-conditioning, maneuvers, holds, takedowns, counters, strategy, and pinning combinations
Includes index
Keywords: Wrestling